Hygroscopic properties of smoke-generated organic aerosol particles emitted in the marine atmosphere - A. Wonaschütz (Atmospheric Chemistry and Physics, 2013)
During the Eastern Pacific Emitted Aerosol Cloud Experiment (E-PEACE), a plume of organic aerosol was produced by a smoke generator and emitted into the marine atmosphere from aboard the R/V Point Sur. In this study, the hygroscopic properties and the chemical composition of the plume were studied at plume ages between 0 and 4 h in different meteorological conditions. In sunny conditions, the plume particles had very low hygroscopic growth factors (GFs): between 1.05 and 1.09 for 30 nm and between 1.02 and 1.1 for 150 nm dry size at a relative humidity (RH) of 92%, contrasted by an average marine background GF of 1.6. New particles were produced in large quantities (several 10 000 cm−3), which lead to substantially increased cloud condensation nuclei (CCN) concentrations at supersaturations between 0.07 and 0.88%. Ratios of oxygen to carbon (O : C) and water-soluble organic mass (WSOM) increased with plume age: from < 0.001 to 0.2, and from 2.42 to 4.96 μg m−3, respectively, while organic mass fractions decreased slightly (~ 0.97 to ~ 0.94). High-resolution aerosol mass spectrometer (AMS) spectra show that the organic fragment m/z 43 was dominated by C2H3O+ in the small, new particle mode and by C3H7+ in the large particle mode. In the marine background aerosol, GFs for 150 nm particles at 40% RH were found to be enhanced at higher organic mass fractions: an average GF of 1.06 was observed for aerosols with an organic mass fraction of 0.53, and a GF of 1.04 for an organic mass fraction of 0.35.